2021
DOI: 10.1093/heapol/czaa137
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the performance of beneficiary targeting in Brazil’s More Doctors Programme

Abstract: Many countries employ strategies that rest on the use of an explicitly defined set of criteria to identify underserved communities. Yet, we know relatively little about the performance of community-level targeting in large-scale health programmes. To address this gap, we examine the performance of community targeting in the More Doctors Programme (MDP). Our analysis covers all 5570 municipalities in the period between 2013 and 2017 using publicly available data. We first calculate the rate at which vulnerable … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 52 publications
0
6
0
3
Order By: Relevance
“…Furthermore, the additional number of doctors provided may have been too small to substantially impact infant health outcomes. Secondly, there is evidence that the PMM doctors were allocated to non-priority municipalities likely limiting their effectiveness and potential to reduce IMR [ 14 , 15 ]. Many PMM doctors were allocated to areas with already low levels of IMR or where there were higher levels of non-PMM primary care doctors working.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Furthermore, the additional number of doctors provided may have been too small to substantially impact infant health outcomes. Secondly, there is evidence that the PMM doctors were allocated to non-priority municipalities likely limiting their effectiveness and potential to reduce IMR [ 14 , 15 ]. Many PMM doctors were allocated to areas with already low levels of IMR or where there were higher levels of non-PMM primary care doctors working.…”
Section: Discussionmentioning
confidence: 99%
“…This study found a lack of association between the PMM and infant health outcomes across strata when stratifying by municipal socio-economic characteristics including poverty and urbanisation. This suggests despite poor targeting of PMM doctors to priority municipalities [ 14 , 15 ], the relationship between the PMM and IMR was not substantially affected by municipal socio-economic factors other than infant mortality. This is generally supported by other studies which report no association between PMM and infant mortality in municipality subgroups of mother’s education, mother’s age and marital status [ 18 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, the More Doctors Program (MDP), a large-scale PHC program that aimed at increasing investments for the FHS, attempted to address this challenge by recruiting domestic and foreign primary care physicians in low-resource communities. 76 Hone and colleagues (2020) found that the MDP led to improvements in physician availability, though this Program has been partially discontinued. 77 Turkey continues to confront similar disparities in the distribution of population health.…”
Section: Discussionmentioning
confidence: 99%
“…81 In congruence with these findings, similar community-level discrepancies were observed in the roll out of the MDP. 76 In Turkey, the MOH remains the main steward in the PHC system. Kringos and colleagues (2015) suggested that the clear delineation of rules and responsibilities in PHC delivery may have contributed to improvements in coordination of care and communication between the MOH and health authorities in provinces, and reductions in cross-provincial variation in the implementation of primary care policies.…”
Section: Discussionmentioning
confidence: 99%